2011
DOI: 10.1111/j.1740-8261.2011.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of Feline Appendicular Degenerative Joint Disease vs. Macroscopic Appearance of Articular Cartilage

Abstract: Degenerative joint disease (DJD) is common in domesticated cats. Our purpose was to describe how radiographic findings thought to indicate feline DJD relate to macroscopic cartilage degeneration in appendicular joints. Thirty adult cats euthanized for reasons unrelated to this study were evaluated. Orthogonal digital radiographs of the elbow, tarsus, stifle, and coxofemoral joints were evaluated for the presence of DJD. The same joints were dissected for visual inspection of changes indicative of DJD and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 29 publications
2
48
0
Order By: Relevance
“…This discordance between pain and radiographic signs is in line with studies in humans, although in human studies the pain is generally self-reported [21-25]. The discordance between pain and radiographic signs may be partly explained by the discordance between radiographic signs and grossly assessed signs of joint degeneration, as highlighted recently in cats [15]. The higher values for SPEC and NPV than SENS and PPV suggest the absence of pain (and crepitus, effusion or thickening) can be used clinically to help rule out DJD with a high(er) degree of certainty.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This discordance between pain and radiographic signs is in line with studies in humans, although in human studies the pain is generally self-reported [21-25]. The discordance between pain and radiographic signs may be partly explained by the discordance between radiographic signs and grossly assessed signs of joint degeneration, as highlighted recently in cats [15]. The higher values for SPEC and NPV than SENS and PPV suggest the absence of pain (and crepitus, effusion or thickening) can be used clinically to help rule out DJD with a high(er) degree of certainty.…”
Section: Discussionsupporting
confidence: 77%
“…Orthogonal radiographs of all joints and the spine were made under sedation using indirect digital flat panel imaging system (Canon Medical CXDI-50 G Sensor, Eklin Medical Systems, Santa Clara, CA). Criteria for evaluation of radiographic signs of feline appendicular joints and axial skeleton DJD were as previously described, [10] and based on the results of other studies that have evaluated the relationship between radiographic DJD and aspects of joint destruction [14,15]. Radiological features that were considered indicative of the presence of DJD in appendicular joints were: joint effusion, osteophytes, enthesophytes, joint-associated mineralization, sclerosis, subchondral bone erosions or cysts and presence of intraarticular mineralization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a radiographic examination, the symptoms of feline joint osteoarthritis are similar to the changes observed in other animal species, but in cats, osteophyte formation usually affects the hip joint. Joint-associated mineralisation is significantly more prevalent in cats than dogs (Freire et al 2011). Densification of the cancellous bone is observed at the insertion site of the ligament of the femoral head (Kamishina et al 2006).…”
Section: Discussionmentioning
confidence: 88%
“…Radiographic evidence of DJD is frequently accompanied by changes in mobility, activity, and social interactions (Lascelles et al, 2010a; Slingerland et al, 2011; Klinck et al, 2012), yet discrepancies exist between radiographic signs, orthopedic exam findings, and owner-reports of impairment (Bennett and Morton, 2009; Freire et al, 2011). Treatment options for this pervasive disease are lacking, in part due to the difficulty in accurately assessing pain and associated disability in cats.…”
Section: Introductionmentioning
confidence: 99%